2018
DOI: 10.1108/jic-12-2017-0185
|View full text |Cite
|
Sign up to set email alerts
|

Should bankers be concerned with Intellectual capital? A study of the Thai banking sector

Abstract: Purpose The purpose of this paper is to examine the causal effect of intellectual capital (IC) performance on financial performance at Thai listed banks. Design/methodology/approach Data are collected from 16 listed banks in Thailand for the period 1997–2016. This paper uses the value-added intellectual coefficient methodology suggested by Pulic (1998, 2004) to measure IC. This study employs a fixed-effects and random-effects model and generalized method of moments (GMM) estimator to investigate the causal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
164
4
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(204 citation statements)
references
References 36 publications
28
164
4
8
Order By: Relevance
“…Firer and Williams [1] also emphasized the importance of PC in improving the sustainable performance of an institution. However, previously, many studies reported the positive impact of CEE on performance [4,6,12,18,[32][33][34]39,41,52,58,63,67,71,75,77], while some reported no relationship between CEE and performance [1,10,35,37,38,43]. We thus, pose the following hypothesis:…”
Section: Cee and Performancementioning
confidence: 76%
See 4 more Smart Citations
“…Firer and Williams [1] also emphasized the importance of PC in improving the sustainable performance of an institution. However, previously, many studies reported the positive impact of CEE on performance [4,6,12,18,[32][33][34]39,41,52,58,63,67,71,75,77], while some reported no relationship between CEE and performance [1,10,35,37,38,43]. We thus, pose the following hypothesis:…”
Section: Cee and Performancementioning
confidence: 76%
“…However, literature has provided mixed evidence about the impact of SCE on performance. Previously, some researchers reported a positive relationship [6,12,33,52,74,81,92,93] and some reported an insignificant relationship between SCE and performance [32,34,39,58,68,69,71,72,75]. Thus, based on the theories and literature, we pose our hypothesis: Hypothesis 4.…”
Section: Sce and Performancementioning
confidence: 82%
See 3 more Smart Citations